Visual optimization of Kutai Kartanegara MSME products in the marketplace as a support for digital marketing - Mohammad Kiswanto; Surahman Surahman; Prapdopo Prapdopo; Sarlivia Sarlivia; Putri Maghfirah Vidhiyanty; Muhammad Noor (Community Empowerment, 2023)
This MSME product marketing digitization assistance program is carried out in the Sebulu sub-district and Kotabangun sub-district, Kutai Kartanegara Regency. The purpose of this community service is to facilitate MSME actors to be able to produce superior regional products by utilizing digitization for product marketing through the marketplace. This program is carried out with the method of mentoring, counseling and direct practice. At the end of the program, MSME actors have been able to produce good product visuals so they can optimize digital marketing through the marketplace to attract potential buyers.